1984
DOI: 10.1136/pgmj.60.702.267
|View full text |Cite
|
Sign up to set email alerts
|

Adult listeriosis—a review of 18 cases

Abstract: Summary Eighteen cases of adult listeriosis (nine with meningitis, one brain abscess and eight bacteraemia) were diagnosed in the Chaim Sheba Medical Center in the years 1964–1982. The infection seemed to be opportunistic in all. Eleven patients had malignant disease, two had cirrhosis of the liver, one had ulcerative colitis, one had bronchial asthma with chronic obstructive pulmonary disease, one had pemphigus, one had diabetes mellitus and one had a renal transplantation. Twelve patients (66%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 5 publications
0
13
0
2
Order By: Relevance
“…We report a case of septicemia after colonoscopy caused by L. monocytogenes in a patient with ulcerative colitis who was receiving corticosteroids and azathioprine. We also review the pertinent previously reported cases (2,7,8). …”
Section: Listeria Monocytogenes (L Monocytogenes) Is a Grampositivementioning
confidence: 99%
See 1 more Smart Citation
“…We report a case of septicemia after colonoscopy caused by L. monocytogenes in a patient with ulcerative colitis who was receiving corticosteroids and azathioprine. We also review the pertinent previously reported cases (2,7,8). …”
Section: Listeria Monocytogenes (L Monocytogenes) Is a Grampositivementioning
confidence: 99%
“…These reported cases and the present cases are reviewed in Table 2 (2,7,8). As no patient suffered from meningitis, one possible explanation of the low frequency of Listeria meningitis in ulcerative colitis is that Listeria organisms are not transferred to the central nervous system by phagocytosis and are killed extracellularly by adequate antibiotic therapy (19).…”
Section: Monocytogenes Was First Implicated As a Cause Of Human DImentioning
confidence: 99%
“…Both patients were elderly and one had an underlying malignancy. Coincidental bowel pathology is a common factor in many cases [21]. However, unlike the majority of L. monocytogenes infections blood cultures are usually negative in cases of prosthetic infections [17].…”
Section: Discussionmentioning
confidence: 99%
“…Listeriosis is an uncommon infection in humans but is probably best known as a cause of neonatal meningitis. It is also well recognized as an opportunistic infection in the elderly and in immuno-compromised patients (Samra et al, 1984). Within the last 5 y there have been a total of 353 isolates reported in the cerebrospinal fluid and/or blood, 103 in patients over the age of 65 y.…”
Section: Discussionmentioning
confidence: 99%